PENGARUH PENGUNGKAPAN CSR, CG, PROFITABILITAS, LEVERAGE DAN SIZE TERHADAP AGRESIVITAS PAJAK - Jepri Yayang Ari Anggara; Faizal Satria Desitama (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Taxation which is considered as a deduction in income is one of the aspect of thestill high level of tax aggressiveness in the world. This research aims to identifywhether CSR, CG, Profitability, Leverage and SIZE contribute to taxaggressiveness. Sampling was selected using a purposive sampling methodthroughseveral criteria to obtain 68 samples of company reports. In analyzing thedata using the classical assumption test, panel data regression analysis andhypothesis testing. The data obtained, obtained directly from the websiteIndonesian Stock Exchange or the official website of each company. The samples,were the annuals reports and sustainability reports for 2018 -2021 years. Theresults of this researh partially show that CSR does not have a significant effect ontax aggressiveness while CG, profitability, leverage have a significant positiveeffect on tax aggressiveness and SIZE has a significant negative effect on taxaggressiveness. Simultaneously displaying CSR, CG, profitability, leverage andSIZE have a significant contribution to tax aggressiveness of 52%. The rest isinfluenced by other aspect not tested in this research.Keywords: CG, CSR, Leverage, Profitability, SIZE, Tax Aggresiveness